Challenges in Pancreatic Cancer 2021
DOI: 10.5772/intechopen.93225
|View full text |Cite
|
Sign up to set email alerts
|

Current Systemic Treatment Options for Metastatic and Unresectable Pancreatic Cancer

Abstract: Metastatic and local advanced unresectable pancreatic cancers are lethal conditions that always carry a poor prognosis with rare exceptions. Currently, the mainstay of therapy is cytotoxic chemotherapy plus best supportive care. First-line therapy for patients with a good performance status includes FOLFIRINOX or gemcitabine plus nab-paclitaxel regimens. Patients carrying a deleterious germline BRCA mutation can be treated with maintenance olaparib after FOLFIRINOX. Patients with a poor performance status, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(48 reference statements)
2
0
0
Order By: Relevance
“…13 In our study, mucositis, neutropenia, and neuropathy were observed in the gemcitabine plus platinum group at a similar rate to that in the literature. 16 These side effects were also detected more frequently in patients receiving FOLFIRINOX compared to those receiving gemcitabine platinum, which is consistent with the literature. 16 However, thrombocytopenia has been detected more frequently than in the literature, and diarrhea is less common than in the literature.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…13 In our study, mucositis, neutropenia, and neuropathy were observed in the gemcitabine plus platinum group at a similar rate to that in the literature. 16 These side effects were also detected more frequently in patients receiving FOLFIRINOX compared to those receiving gemcitabine platinum, which is consistent with the literature. 16 However, thrombocytopenia has been detected more frequently than in the literature, and diarrhea is less common than in the literature.…”
Section: Discussionsupporting
confidence: 89%
“…16 These side effects were also detected more frequently in patients receiving FOLFIRINOX compared to those receiving gemcitabine platinum, which is consistent with the literature. 16 However, thrombocytopenia has been detected more frequently than in the literature, and diarrhea is less common than in the literature. [4][5][6] In our study, the combination of gemcitabine and platinum-enhanced chemotherapy seemed more tolerable than FOLFIRINOX group.…”
Section: Discussionsupporting
confidence: 89%